1999
DOI: 10.1093/bja/82.5.672
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bispectral EEG analysis and auditory evoked potentials for monitoring depth of anaesthesia during propofol anaesthesia

Abstract: We have compared the auditory evoked potential index (AEPIndex) and bispectral index (BIS) for monitoring depth of anaesthesia in spontaneously breathing surgical patients. Twenty patients (aged 17-49 yr) undergoing day surgery were anaesthetized with computer-controlled infusions of propofol. The mean (SD and range) of each measurement was determined during consciousness and unconsciousness and at specific times during the perioperative period. Mean values for AEPIndex during consciousness and unconsciousness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 22 publications
4
30
0
2
Order By: Relevance
“…The higher stability of volatile anesthesia probably arises from the monitoring of end-tidal concentration of volatile anesthetic. Good correlation between AAI and concentration of both volatile 32,39,41,45,46 and intravenous anesthetics 21,37,38,47 during anesthesia was observed. At the end of surgery, together with decreasing concentration of volatile anesthetics, both AAI values and clinical parameters increased till the reversal of anesthesia.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The higher stability of volatile anesthesia probably arises from the monitoring of end-tidal concentration of volatile anesthetic. Good correlation between AAI and concentration of both volatile 32,39,41,45,46 and intravenous anesthetics 21,37,38,47 during anesthesia was observed. At the end of surgery, together with decreasing concentration of volatile anesthetics, both AAI values and clinical parameters increased till the reversal of anesthesia.…”
Section: Discussionmentioning
confidence: 75%
“…The observations of others [37][38][39] showed the higher sensitivity of auditory evoked potentials in comparison to spontaneous electroencephalogram in evaluating the changes of consciousness. During induction of anesthesia, together with decrease in AAI, in both groups also heart rate and systemic blood pressure decreased.…”
Section: Discussionmentioning
confidence: 92%
“…In several studies AAI have been shown to reduce the amount of anaesthetics given and expedite immediate postoperative recovery as compared to standard practice [7] [8]. A number of studies have also demonstrated that the sensitivity and specificity for AAI is not perfect [9] [10] and fears have been raised that the incidence of awareness might even increase if the anaesthetist aims at an upper threshold value [11] [12].…”
Section: Discussionmentioning
confidence: 99%
“…The BIS values in our sample were generally lower than is recommended for surgical anaesthesia [11] and low in comparison with other adult studies. Mean intra-operative BIS has ranged from 32.4 to 72 [16][17][18][19][20][21][22][23][24][25] and median BIS has ranged from 36 to 48 [26][27][28][29], none as low as the mean of 28.1 and the median of 25.4 in our patients, with the exception of two trials, one where relatively high doses of anaesthetic were used to control haemodynamic changes [25] and another where there was little surgical stimulation [20] and the mean intra-operative BIS was 42-72. A recent study of 164 patients undergoing a variety of major and minor surgical procedures found BIS < 40 for 26 (22)% of the BIS-guided TCI maintenance of anaesthesia (mean (SD)) compared to 88.8 (19.75)% for our sample [18].…”
Section: Discussionmentioning
confidence: 99%